PENGAWASAN DPRD TERHADAP PENERAPAN PERATURAN DAERAH TENTANG IZIN MENDIRIKAN BANGUNAN DALAM PERSPEKTIF HUKUM ISLAM - Zainuddin Mustapa; A. Gunawan Ratu Chakti (Al-Amwal : Journal of Islamic Economic Law, 2023)
Islamic law is considered as an important part of religious teachings in the view of Muslims, and as such Islamic law is the main space for expression of religious experience and becomes a determinant of historical continuity and identity. In line with the increasing awareness to return to pure and original religion and the emergence of a desire to harmonize contemporary life with the provisions of sharia, Islamic law in modern times has received a lot of attention from both its own supporting community and from other societies which make it an object of study. Islamic law is a law revealed by Allah to humans to ensure the realization of benefit for humans themselves, both in this world and in the hereafter. The deeper a person's knowledge of the essence of Islamic law, the greater the value of goodness and benefit he will get. The aims of this research are: (1) to find out and analyze the effectiveness of the DPRD's supervision of the application of building permits from the perspective of Islamic law; (2) Knowing the factors that influence the effectiveness of DPRD supervision on the application of Regional Regulation Number 4 of 2012 concerning Building Permits from the perspective of Islamic Law. The results of the study show that: The DPRD's supervision of the implementation of the Perda on Building Permits from the perspective of Islamic law in the City of Palopo is not effective, so it is necessary to make efforts to make it effective through efforts to socialize the Perda in order to regulate and control settlement development and increase local revenue. PAD) City of Palopo. Furthermore, the factors that influence the implementation of DPRD supervision of the implementation of Regional Regulation Number 4 of 2012 concerning Building Permits in the City of Palopo, include: factors of legal structure, legal substance, legal culture, facilities and infrastructure, legal awareness, and community support.